1993
DOI: 10.1254/jjp.62.75
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of β-Adrenergic Systems in the Antagonizing Effect of Paeoniflorin on the Scopolamine-Induced Deficit in Radial Maze Performance in Rats

Abstract: ABSTRACT-Whether anaphylactic histamine release from rat peritoneal mast cells is influenced by betahistine, a histamine H1-receptor agonist/H3-antagonist, and dimaprit, an H2-agonist, was examined.Treatment with dimaprit at 6 and 60 uM for 20 min significantly inhibited the anaphylactic histamine release, whereas betahistine at up to 80 pM under the same conditions did not affect it. Treatment with dimaprit at 6 and 60 pM for 1 to 20 min and for 5 to 20 min, respectively, caused a time-dependent inhibi tion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 33 publications
2
6
0
Order By: Relevance
“…Taking this report into consideration together with our previous report (26) on the inhibition of anaphylactic histamine release by dimaprit described above and the relatively high concen trations of a-MH necessary to inhibit the release in the present results, it is suggested that H3-receptors on the rat peritoneal mast cell are a subtype distinct from those in the rat brain.…”
Section: Histamine Levels In Rat Plasmassupporting
confidence: 82%
See 1 more Smart Citation
“…Taking this report into consideration together with our previous report (26) on the inhibition of anaphylactic histamine release by dimaprit described above and the relatively high concen trations of a-MH necessary to inhibit the release in the present results, it is suggested that H3-receptors on the rat peritoneal mast cell are a subtype distinct from those in the rat brain.…”
Section: Histamine Levels In Rat Plasmassupporting
confidence: 82%
“…Besides the present results that a-MH decreased the anaphylactic histamine release from isolated rat mast cells, we have recently found that dimaprit (H2-agonist) (22) at relatively high concentrations of 0.6 to 60 pM also concentration-dependently decreased the release, which was restored by the coexistence of thioperamide, but not by mepyramine and cimetidine, while betahistine [H, agonist (23)/H3-antagonist (24,25)] does not influence the anaphylactic histamine release (26). On the other hand, as shown in the present results, dimaprit and a-MH as well as betahistine trivially influenced compound 48/80-induced histamine release.…”
Section: Histamine Levels In Rat Plasmassupporting
confidence: 62%
“…Thioperamide is now described as a selective H3/4R antagonist . As the H4R was not yet discovered at the time of their observation, the authors concluded that H3R‐like receptors were responsible for the negative feedback regulation of histamine . Based on our current findings that indeed, the H4R plays a role in FcεRI‐dependent processes by inhibiting basophil activation and degranulation, we can assume that the suppressive effect on the histamine release in their study was at least in part attributable to the H4R.…”
Section: Discussionmentioning
confidence: 58%
“…In contrast to the study with human leukocytes , the H2R antagonist cimetidine did not affect the decreased release of histamine from rat peritoneal mast cells. Interestingly, the reduced release could be dose dependently restored by thioperamide . Thioperamide is now described as a selective H3/4R antagonist .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation